2015
DOI: 10.1007/s10551-015-2823-x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Particular and Universal: Dependence, Independence, and Interdependence of Context, Justice, and Ethics

Abstract: This article reflects on context effects in the study of behavioral ethics and organizational justice. After a general overview, we review three key challenges confronting research in these two domains. First, we consider social scientific versus normative approaches to inquiry. The former aims for a scientific description, while the latter aims to provide prescriptive advice for moral conduct. We argue that the social scientific view can be enriched by considering normative paradigms. The next challenge we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…This said, our final call is for more research at the intersection of CSR and organizational justice. While great strides are being made to integrate the organizational justice and behavioral ethics literatures (e.g., Crawshaw et al, 2013;Fortin, Nadisic, Bell, Crawshaw, & Cropanzano, 2016), we see similar opportunities here. Rupp's (2011) work articulating the potential alternative employee and executive motives for CSR importance provide a potentially useful startpoint and framework.…”
Section: Limitations and Future Researchmentioning
confidence: 72%
“…This said, our final call is for more research at the intersection of CSR and organizational justice. While great strides are being made to integrate the organizational justice and behavioral ethics literatures (e.g., Crawshaw et al, 2013;Fortin, Nadisic, Bell, Crawshaw, & Cropanzano, 2016), we see similar opportunities here. Rupp's (2011) work articulating the potential alternative employee and executive motives for CSR importance provide a potentially useful startpoint and framework.…”
Section: Limitations and Future Researchmentioning
confidence: 72%
“…A motivated cognition perspective can also be used as a foundation to facilitate meaningful integration between the fairness literature and other domains, including moral judgments, behavioral economics, ethical decision making, and behavioral ethics. Consider behavioral ethics as an example—numerous scholars have advocated for integration between behavioral ethics and fairness (e.g., Crawshaw, Cropanzano, Bell, & Nadisic, 2013; Cropanzano & Stein, 2009; Folger et al, 2005; Fortin, Nadisic, Bell, Crawshaw, & Cropanzano, 2016; Schminke, Ambrose, & Noel, 1997). An interesting find was that the reasons for proposed integration are often (implicitly) related to motivated cognitions (e.g., the presence of similar motives, the importance of identity; e.g., Skitka, 2003).…”
Section: Creating a Path Forward: Leveraging Insights From Motivated ...mentioning
confidence: 99%
“…Studies on empathy have generally followed a two-dimensional perspective: The cognitive perspective—mental perspective taking—[88,97,98], and the emotional perspective—the vicarious sharing of emotion—[87,99,100]. Recent studies have found that “both cognition and affect are important, but more research is needed to determine how they work together” [101]. Some authors also consider it to be a trait—dispositional empathy—or state—situational empathy—in both interpersonal relationships and relationships with nature [22].…”
Section: Introductionmentioning
confidence: 99%